The Effectiveness of PBL Assisted by Digital Storytelling Media towards Science Literacy and Critical Thinking Skills (Universitas Negeri Semarang, 2020)
The ability of scientific literacy and critical thinking are very important possessed by student. Many researchers suggested that Problem Based Learning (PBL) could enhance the students’ scientific literacy and critical thinking. The use of digital storytelling media is believed to help motivate students to focus more and joyfull on learning. Therefore the study aimed to investigate the effectiveness of PBL assisted by digital storytelling media to improve the scientific literacy and critical thinking skills of fifth graders of elementary school students. This study used a mixed-methods with explanatory sequential design. Research data were collected through written tests, questionnaires, and interviews. Classical completeness tests, N-gain test, and independent sample t-test were used to test the effectiveness of the treatment. The results of triangulation analysis of the questionnaire, observation, and interview data shown that PBL learning models assisted by digital storytelling media are effective in improving students’ science literacy and critical thinking skills.The digital storytelling media has helped students to understand the context, are more motivated to learn, and could facilitated students to be more critical and literate in understanding problems.